Perlindungan dan Hubungan Hukum Para Pihak Dalam Fleksibilitas Ekonomi Gig di Indonesia - Tampubolon, Boy Joshua P.; Holyness N. Singadimedja; Rubiati, Betty (Fakultas Hukum Universitas Islam Malang, 2025)
The rapid growth of the digital economy has given birth to a flexible working model known as the gig economy. In Indonesia, this system offers ease in work dynamics, but also creates vulnerabilities for its workers. This study uses a normative juridical approach with literature and field study methods. The purpose is to examine the legal relationship between the parties in gig work practices based on labor regulations and the Civil Code, as well as evaluate forms of legal protection for gig workers in partnership relationships to support their welfare. The lack of an element of command in the employment relationship between platforms and gig workers leads to limited access to the protection of labor rights, such as social security and wages. Therefore, a comprehensive and adaptive regulatory framework is needed to ensure protection for gig workers without hindering the operational flexibility of digital platforms.